Pengaruh advertising terhadap purchasing intention - prasetian, Agan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The development of the restaurant industry is still an important sector in increasing national income. This study aimed to determine the effect of advertising on purchasing Intention in KFC Metro Bandung customers. In conducting this research, the writer uses a descriptive method. Field research (field research), namely conducting research directly to consumers by distributing questionnaires. The results of this study show a strong relationship between KFC Advertising and Consumer Purchasing Intention, and based on the calculation of the coefficient of determination, a value of 30.14 is obtained. This shows that KFC Advertising influences consumer Purchasing Intention